2010
DOI: 10.1002/ana.22050
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy and embolic signal in cancer patients with ischemic stroke

Abstract: A high prevalence of ES was observed in cancer patients with ischemic stroke, especially in those without CSMs. Elevated D-dimer levels were independently associated with ES, and decreased dramatically with the use of anticoagulants. ANN NEUROL 2010;68:213-219.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 29 publications
(40 reference statements)
12
130
0
4
Order By: Relevance
“…15,16 Because of the advances in cancer medicine and the steadily increasing proportion of elderly people, the number of people living with cancer is increasing. As a consequence, the proportion of patients who have cancer is expected to increase among patients with stroke, especially in those without other stroke pathogeneses.…”
Section: Evaluation Of Cryptogenic Stroke With Advanced Diagnostic Tementioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Because of the advances in cancer medicine and the steadily increasing proportion of elderly people, the number of people living with cancer is increasing. As a consequence, the proportion of patients who have cancer is expected to increase among patients with stroke, especially in those without other stroke pathogeneses.…”
Section: Evaluation Of Cryptogenic Stroke With Advanced Diagnostic Tementioning
confidence: 99%
“…The detection of an embolic signal with TCD may provide clues on the cancer-specific mechanism related to hypercoagulopathy and may be used to monitor the effect of treatment in the acute stroke period. 16 Unlike nonbacterial thrombotic endocarditis, 61 these patients usually had multiple small diffusion-weighted imaging (DWI) lesions with microembolic signals on TCD monitoring, and TEE usually did not reveal vegetations, suggesting intravascular coagulopathy. …”
Section: Workup For Cancer-related Coagulopathymentioning
confidence: 99%
“…5,11,12 A recent Korean multicenter study showed that 60% of stroke events among cancer patients are associated with conventional mechanisms, such as atherosclerotic and cardioembolic causes. The remaining 40% are of the cryptogenic mechanism, likely including cancer-related causes.…”
Section: Discussionmentioning
confidence: 99%
“…Suggesting microembolic mechanisms in those patients, the incidence of high-intensity transient signals correlated significantly with d-dimer levels in patients not displaying conventional stroke mechanisms. 14 These results have recently been reviewed by Bang et al in 2011 15 ; however, neither study included a control group and both studies are still expecting replication outside South Korea.…”
Section: Strokementioning
confidence: 92%